The association between serum serglycin level and coronary artery disease severity in patients with stable angina pectoris - Bolayir, Hasan Ata; Kivrak, Tarik; Gunes, Hakan; Bolayir, Asli; Karaca, Ilgin (Via Medica, 2018)
Background: Serglycin plays a key role in the inflammatory status however the relationship between coronary artery disease (CAD) and serglycin is still unknown. Aim: In this study, we aimed to investigate association of serglycin levels with CAD severity in patients with stable angina pectoris (SAP). Methods: In total, 100 SAP patients diagnosed by coronary angiography and clinical manifestations, and 100 control subjects matched for age and sex were enrolled in this case-control study. Plasma levels of serglycin, high-sensitivity C-reactive protein (hsCRP), lipid profiles, and clinical parameters were assayed for all participants. The severity of coronary lesions was evaluated based on the SYNTAX score (SS) assessed by coronary angiography. Results: Positively correlated with the SS (r = 0.564, p < 0.001), the plasma serglycin level in the SAP group was higher than that in the control group (11.17 +/- 1.82 vs. 19.28 +/- 1.88 ng/mL, p < 0.001). The plasma serglycin level was an independent predictor for both SAP (odds ratio [OR] 1.037, 95% confidence interval [CI] 1.020-1.054, p < 0.001) and a high SS (OR = 1.087, 95% CI 1.051-1.124, p < 0.001) in a multivariate logistic regression model. In the receiver operating characteristic curve analysis, the plasma serglycin level was found to have a better predictive value for a high SS (area under the curve [AUC] 0.858, 95% CI 0.788-0.929, p < 0.001) compared with hsCRP (AUC 0.665, 95% CI 0.557-0.773, p = 0.006; Z = 2.94, p < 0.001), with an optimal cut-off value of 17.25 ng/mL (sensitivity 94.3%, specificity 68.2%). Conclusions: Plasma serglycin levels correlate with both the presence and severity of coronary stenosis in patients with SAP, suggesting that it could be a potential predictive marker of severe stenosis in SAP patients.
Keywords: serglycin; coronary artery disease; SYNTAX score; inflammation; stable angina pectoris